Validitas Penuntun Praktikum Berbasis PjBL Untuk Menanamkan Karakter Profil Pelajar Pancasila Materi Proses Pengaturan Tumbuhan - Ihsan, Afifi Raima; Ayatusa’adah, Ayatusa’adah; Rohmadi, Mukhlis (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The development of practicum guides in the form of flipbooks based on project base learning (PjBL) is easy to use and is expected to instill the character of the Pancasila student profile in accordance with the demands of the Independent Curriculum. This study aims to test the validity of PjBL-based practicum guidance on the process of plant management in class XI. This research is Research and Development by following the Borg and Gall model procedure, which consists of four stages: (1) research and data collection, (2) product planning, (3) product development, and (4) product validation. The instrument used in this study is in the form of a validation questionnaire. The data collection technique of this research is through filling out a questionnaire filled out by 2 material experts and 2 media experts who are lecturers at IAIN Palangka Raya as validators for practicum guidance. The validation results showed that (1) the validity in terms of material with an average increased from 74% in the first stage and to 83.6% in the second stage, thus changing the category from valid to very valid; (2) the validity in terms of media results in the first stage with an average of 79% increased to 84.4% in the second stage and changed the category from valid to very valid. Thus, that the developed practicum guide can be tested at the next stage of development.